Design and Development of an Augmented Reality Learning Medium for the Conservation of the Endemic Flora Balikpapan Ginger (Etlingera balikpapanensis) - Fulkha Tajri M; Olivia Febrianty Ngabito; Denny Huldiansyah; Azzah Nafisah Sofyan; Muhammad Bintang Kurniawan; Surya Abdi Pratama (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2026)
Balikpapan Ginger (Etlingera balikpapanensis) is an endemic flora of East Kalimantan with significant ecological, historical, and economic value, yet it remains largely unknown among the general public, particularly students. This condition highlights the need for innovative learning media to support environmental awareness and conservation education in a more engaging and accessible manner. Although Augmented Reality (AR) has been widely applied in environmental and biological education, prior studies mainly focus on general species and lack contextual integration of locally endemic flora into conservation learning. This study addresses this gap by developing a location-specific AR-based learning application that integrates scientific botanical data with interactive visualization to enhance local environmental literacy. The development process follows the Multimedia Development Life Cycle (MDLC), including concept, design, material collection, assembly, testing, and distribution. The evaluation involved 15 respondents, including administrators and adult visitors of the Balikpapan Botanical Garden, using a five-point Likert scale to assess technical feasibility, educational value, engagement potential, conservation relevance, and technical stability. The results indicate a high level of acceptance, particularly in educational value and engagement aspects, demonstrating the effectiveness of the application as a learning medium. These findings suggest that AR-based applications can support environmental education by providing immersive and interactive learning experiences aligned with constructivist learning theory and Mayer’s Cognitive Theory of Multimedia Learning